Single-and Dual-Band Bandpass Filters Based on Multiple-Mode Folded Substrate-Integrated Waveguide Cavities - Liu, Qing; Zhang, De-Wei; Gong, Ke; Qian, Hang; Qu, Wei-Zhe; An, Na (IEEE transactions on microwave theory and techniques, 2023)
High-selective bandpass filters (BPFs) based on novel multiple-mode substrate-integrated waveguide (SIW) cavities are proposed in this article. The multiple-mode SIW cavities are realized by a method of folded SIW (FSIW) structure, and its characteristics are analyzed in detail. Dual modes TE _{102} and TE _{201} in the normal SIW as well as modes TE _{1/2,0,1/2} , TE _{1/2,0,3/2} , and TE _{3/2,0,1/2} in the FSIW can be exploited to realize multiple-mode cavities for BPFs' design because their resonant frequencies can be controlled flexibly. To demonstrate the multiple-mode SIW filters' design, two single-band triple-mode SIW BPFs with three finite-transmission zeros (FTZs) are proposed first. Then, dual-band and single-band quad-mode SIW BPFs with four FTZs are proposed. FTZs' locations of the proposed filters can be controlled well, and their controllability is analyzed. Finally, three SIW filters are designed, fabricated, and measured to verify the proposed filters and method. The proposed multiple-mode SIW filters have the advantages of high selectivity, compact size, and flexibly controllable FTZs' locations and bandwidth (BW).